MEDIA KOMIK SEBAGAI UPAYA PENINGKATAN PENGUASAAN KOSAKATA DALAM PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) - Randi Ramliyana (Riksa Bahasa, 2016)
This study used a qualitative method with case study approach. The purpose of this study describes the use of comics media to increase vocabulary of participants in learning Indonesian for Foreign Speakers (BIPA) at Trisakti University Language Center. One of the biggest problems faced in learning vocabulary BIPA is a lack of participants, especially first participants learn Indonesian. To improve the vocabulary of participants is to give something extraordinary and new in BIPA learning, especially among participants adolescence and early adulthood. The results showed that comics can be used efficiently to improve the mastery of vocabulary BIPA participants. Therefore, the use of comics into learning will have the same impact with the use of the method of learning the game in BIPA. It provides a pleasant atmosphere in the classroom. Comics are not just entertaining and engaging participants, but many benefits in learning BIPA.